1993
DOI: 10.1152/jappl.1993.74.4.1492
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of antigen-induced airway and cutaneous responses by heparin: a pharmacodynamic study

Abstract: We have previously shown that heparin attenuates the acute bronchoconstrictor response and immediate cutaneous reaction (ICR) to antigen in allergic sheep. In the present investigation, we studied the pharmacodynamics of the antiallergic action of heparin. Specific lung resistance (sRL) was measured in eight sheep, allergic to Ascaris suum antigen, before and 5 min after inhalation challenge with the antigen. On different experiment days, antigen challenge was repeated after pretreatment with 1) aerosol hepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 0 publications
3
27
1
Order By: Relevance
“…However, heparin was itself able to inhibit the activation of lung mast cells, at least with antiIgE as the stimulus. This is consistent with a previous report by Ahmed et al (1993) who found that addition of heparin to human uterine and rat peritoneal mast cells reduced the degree of IgE-dependent histamine release. Heparin may have mutually antagonistic roles in inhibiting histamine release and in allowing tryptase to act as a stimulus, and this makes it more difficult to assess the contribution of tryptase as an amplification signal.…”
Section: Discussionsupporting
confidence: 94%
“…However, heparin was itself able to inhibit the activation of lung mast cells, at least with antiIgE as the stimulus. This is consistent with a previous report by Ahmed et al (1993) who found that addition of heparin to human uterine and rat peritoneal mast cells reduced the degree of IgE-dependent histamine release. Heparin may have mutually antagonistic roles in inhibiting histamine release and in allowing tryptase to act as a stimulus, and this makes it more difficult to assess the contribution of tryptase as an amplification signal.…”
Section: Discussionsupporting
confidence: 94%
“…Our failure to show an inhibitory effect of inhaled heparin on sodium metabisulphite-induced bronchoconstriction is unlikely to be due to the timing of the challenge after heparin inhalation, since time course studies have shown that the inhibitory effect of inhaled heparin on allergen-induced bronchoconstriction in Ascaris suum sensitive sheep is maximal less than 20 min after inhalation [4]. Our negative findings may reflect problems with access of inhaled heparin to cholinergic nerve endings.…”
Section: Discussionmentioning
confidence: 62%
“…Heparin has a number of anti-inflammatory effects including, inhibition of mast cell mediator release [3,4], inhibition of aspects of lymphocyte activation [10], and limitation of the injurious effect of major basic protein [9], and it has been suggested that it serves a defensive role in the airways [11]. Our study suggests that this defensive role does not extend to inhibition of neurallyinduced bronchoconstriction at least if heparin is administered by inhalation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The therapeutic effect of heparin is based on many studies and therapeutic trials [38,44,45,46,47,48,49,50,51]. The concept of our thesis has been seen in other allergic responses [38,44,45,46,47,48,49,50,51].…”
Section: Discussionmentioning
confidence: 99%